2019
DOI: 10.3390/educsci9030200
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation as a Basic Element of the Professional Culture of Engineers

Abstract: This paper addresses the problem of the formation of the self-regulation of educational activities of students studying in a technical university. The purpose of this paper is to discuss the problem of the self-regulation of educational activities of students, presenting data from an experimental study of students’ self-regulation. Special attention is paid to the distinction between the terms self-control and self-regulation. This paper presents data on the state of self-regulation among students studying tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 63 publications
0
12
0
2
Order By: Relevance
“…Many researchers highlighted this affective domain for development of character education programs (Yeager et al, 2014;Anam et al, 2019). For example, selfregulation skills differ among gifted students (Tortop, 2015), self-improvement depends on regulation (Odinokaya et al, 2019), become an independent learner (Sholeh, 2019), SRL skills impact learning interest (Kizilcec et al, 2017), and the application of various teaching methodologies in SRL (Siddiqui & Malik, 2019), improve reasoning for students (Roslan et al, 2014), develop better understanding (Suardi & Hamid, 2013), emphasis on skills (Greene et al, 2015), strategic activities play an important role in learning (Isohätälä et al, 2017), helping them to think critically (Ratminingsih et al, 2017), improve metacognition and cognitive abilities (Pantiwati, 2017), shifting from the task understanding stage to monitoring activities (Järvelä et al, 2016). From that point on, character education training programs have formed attributes to develop graduates.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers highlighted this affective domain for development of character education programs (Yeager et al, 2014;Anam et al, 2019). For example, selfregulation skills differ among gifted students (Tortop, 2015), self-improvement depends on regulation (Odinokaya et al, 2019), become an independent learner (Sholeh, 2019), SRL skills impact learning interest (Kizilcec et al, 2017), and the application of various teaching methodologies in SRL (Siddiqui & Malik, 2019), improve reasoning for students (Roslan et al, 2014), develop better understanding (Suardi & Hamid, 2013), emphasis on skills (Greene et al, 2015), strategic activities play an important role in learning (Isohätälä et al, 2017), helping them to think critically (Ratminingsih et al, 2017), improve metacognition and cognitive abilities (Pantiwati, 2017), shifting from the task understanding stage to monitoring activities (Järvelä et al, 2016). From that point on, character education training programs have formed attributes to develop graduates.…”
Section: Introductionmentioning
confidence: 99%
“…In the virtual classroom-based learning process, selfregulation becomes very important, because it is a factor that controls student performance but other facts were obtained from the results of the statistical analysis above, it can be concluded that prior knowledge has a significant impact on students' self-regulated learning in virtual classroom learning. Students of modern schooling face mental and eager self-regulation difficulties (Odinokaya et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A special virtual laboratory was created for the course of International Business that is taught in English. Students work at the laboratory during the first stage of integrated learning [76][77][78][79][80]. The laboratory contains video materials, case studies and exercises for the initial training and lecture preparation.…”
Section: The Model Of a Virtual Bilingual Professional Laboratorymentioning
confidence: 99%